SOSIALISASI NILAI DAN NORMA PADA ANAK SEKOLAH MINGGU OLEH PENGURUS BIDANG PELAYANAN KATEGORIAL ANAK GPIB SILOAM DI MASA PANDEMI COVID-19 - Agustinus Catur Krisnugroho; Yohanes Bahari; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the socialization of values and norms to Sunday School childrenby the GPIB Siloam Children's Categorical Services Division during the COVID-19pandemic. The method used is a qualitative method with descriptive analysis. Datacollection tools using observation guidelines, interview guidelines and documentation. Theresults of this study are (1)Social values that are socialized are generally spiritual valuesconsisting of truth values, beauty values, moral values and religious values. These socialvalues and norms are socialized by the management through sermons accompanied bymedia and learning activities. (2)The way to socialize values and norms uses a socializationpattern that tends to be participatory, although in practice, communication tends to be one-way communication. (3)The obstacles in the socialization of social values and norms aremore rooted in the pandemic itself and no problems are found that originate in SundaySchool children. (4)Most children respond well to the transfer of values and norms by theadministrators and apply them in their daily lives. But keep in mind that parents still havea big role in the development of children to apply values and norms in everyday life. (5)Thesocialization provided by seniors and administrators in Sunday Schools through sermonsand assignment activities brought good results. Characterized by children can understandthe social roles of parents in their environment.Keywords : Socializations, Sunday School Children, COVID-19 pandemic